Determinants of Unemployment Rate in Indonesia: A Dynamic Panel Data Approach - Munawaroh, Siti Rizqiyatul; Endang; Susilo, Joko Hadi; Astuti, Hartiningsih (Jurnal Ekonomi Pembangunan, 2025)
Unemployment is a common problem faced by developing countries such as Indonesia. As one of the indicators of economic development, unemployment has a complex nature and has an impact on various aspects. This study was conducted to determine the conditions and variables that affect the unemployment rate in Indonesia from 2014-2023. The data analysis used is a dynamic panel data econometric model using Generalized Method Moments (GMM). This model was developed by Arellano Bond that meets the criteria of unbiased, valid, and consistent. The results of the analysis show that the variables of economic growth, human development index, average years of schooling, total population, foreign direct investment, domestic investment, and number of poor people have a significant effect on the unemployment rate. In addition, the unemployment rate in the previous period also had a significant effect on the unemployment rate in the period when the study was conducted. The findings in the study provide information on strategies to stabilize labor demand and supply, increase investment, and implement efficient short-run and long-run policies as an effort to reduce unemployment in Indonesia.